Chromium(VI) removal from aqueous solution and industrial wastewater by modified date palm trunk. Issue 2 (27th June 2014) - Yadav, Sunil Kumar; Sinha, Shishir; Singh, Dhruv Kumar
Abstract : Date palm trunk (DPT) was grafted with diethylenetriamine (DETA) followed by triethylamine amine (TEA) using epichlorohydrin as a crosslinking agent. The potential of modified date palm trunk (MDPT) for the effective removal of Cr(VI) from aqueous solution has been investigated. The equilibrium was attained with in ∼30 min at optimum pH ∼3.5. The equilibrium adsorption capacity of MDPT increases (49.8 to 89.3 mg/g) as the initial Cr(VI) concentration increases (50–100 mg/L). An adsorbent dosage of 1.2 g/L can remove Cr(VI) up to 99.95% from its solution (100 mg/L). The adsorption behavior of Cr(VI) is best described by the pseudo‐second order model and the calculated equilibrium capacity (90.9 mg/g) agree with the experimental value (89.3 mg/g). Langmuir, Freundlich, and Temkin adsorption isotherm models were applied to represent adsorption data. The equilibrium data were well fitted by the Langmuir isotherm model by revealing the maximum sorption capacity of MDPT (129.8 mg/g). The mechanism of adsorption was also studied using Fourier transform‐infrared (FT‐IR) spectroscopy and scanning electron microscopy (SEM) analysis. Adsorption‐desorption studies reveal that MDPT can be used successfully for four cycles with a small recovery loss (5.4%). Recovered Cr(VI) can be reused beneficially for industrial application. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 452–460, 2015